BIOSINTESIS SELULOSA OLEH Acetobacter xylinum MENGGUNAKAN LIMBAH CAIR TAHU SEBAGAI MEDIA PERTUMBUHAN DENGAN PENAMBAHAN MOLASE - Febrianti, Novi (Universitas Sebelas Maret, 2011)
ABSTRACT Cellulose is a biopolymer whose numbers most abundant in nature and have an important role as various kinds of industrial raw materials. In this study, liquid waste of soy used as a growth medium for A. xylinum bacteria to synthesize cellulose with addition of molasses as carbon source. The aim of this research was to know the effect of different concentrations of molasses on cellulose layer weight and which is the best concentration of molasses that produce the highest weight of cellulose. Three concentration of molasses were tested, namely 2%, 4% and 6%. Observation on layer cellulose weight produced was performed on day-10 . The study shows that the more concentrations of molasses is given, the more weight of the layer of cellulose, although this weight difference was not significant. 6% molasses concentration produces the most high cellulose weight. keywords: cellulose , molase, liquid waste of soy, A. xylinum